From SERVQUAL to Loyalty: A Review of Evidence in Primary Care - Panuturi Ratih Elizabeth Thresna Sinaga (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Service quality plays a vital role in shaping patient satisfaction and loyalty, yet most existing evidence comes from hospital settings. Understanding how service quality functions in primary care is crucial to improving patient experiences and strengthening health system trust. Objective : To map and synthesize empirical findings on the relationships between SERVQUAL dimensions, patient satisfaction, and patient loyalty in primary care services from 2020–2025. Research Methods/ Implementation Methods : A narrative review was conducted using 34 eligible studies that examined SERVQUAL dimensions—tangibles, reliability, responsiveness, assurance, and empathy—in relation to satisfaction and loyalty. Data were extracted on significant predictors, research design, and analytical approaches. Results : Responsiveness, empathy, and tangibles consistently showed the strongest influence on satisfaction, which often mediated the effect of service quality on loyalty. Findings for reliability and assurance varied by context. Most studies used cross-sectional survey designs with SEM-PLS analysis, and heterogeneity in instruments limited quantitative comparison. Conclusion/Lesson Learned : Evidence supports a quality–satisfaction–loyalty pathway in primary care. Future research should standardize instruments, include contextual variables such as financing models (e.g., BLUD), and adopt longitudinal designs to enhance causal interpretation and policy relevance